The influence of the psychological contract on employee engagement in a South African bank - Ngobeni, Dzunani A.; Saurombe, Musawenkosi D.; Joseph, Renjini M. (Frontiers in Psychology, 2022)
The workplace is characterised by numerous contracts of agreement that an employee and employer must sign to formalise their employment relationship. The informal agreement, known as the psychological contract, is often overlooked, although it is pivotal in determining the engagement of employees in an organisation. This study aimed to probe the perceptions line managers have of the influence of the psychological contract on employee engagement in a South African bank with a particular focus on how the integration of technologies from the Fourth Industrial Revolution may have impacted the workplace in the banking sector. The study was carried out using a qualitative research approach. A purposive random sampling strategy was used to select participants who were interviewed using semi-structured, one-on-one interviews. The data collected were analysed using thematic analysis, and verbatim quotes were used to support emergent themes. The findings of the study revealed that continuous change in the world, exacerbated by the COVID-19 pandemic, influences employee expectations. Thus, organisations must be able to quickly adapt and adjust their talent attraction and retention mechanisms. Talent management, the nature of the business, structure and operations, the nature of the work environment, and emotional needs are the themes that emerged from the study. With the constant change in the world of work, including industry disruptions continually imposed by the 4IR and other factors, employees’ expectations are ever-changing. Thus, organisations must keep adapting to attract and retain talent. This study adds value by addressing various aspects aligned with competitively adjusting to the current and future world of work.